Towards effective monitoring of tropical phenology: maximizing returns and reducing uncertainty in long‐term studies. (May 2018) - Bush, Emma R.; Bunnefeld, Nils; Dimoto, Edmond; Dikangadissi, Jean‐Thoussaint; Jeffery, Kathryn; Tutin, Caroline; White, Lee; Abernethy, Katharine A.
Abstract: Phenology is a key component of ecosystem function and is increasingly included in assessments of ecological change. We consider how existing, and emerging, tropical phenology monitoring programs can be made most effective by investigating major sources of noise in data collection at a long‐term study site. Researchers at Lopé NP, Gabon, have recorded monthly crown observations of leaf, flower and fruit phenology for 88 plant species since 1984. For a subset of these data, we first identified dominant regular phenological cycles, using Fourier analysis, and then tested the impact of observation uncertainty on cycle detectability, using expert knowledge and generalized linear mixed modeling (827 individual plants of 61 species). We show that experienced field observers can provide important information on major sources of noise in data collection and that observation length, phenophase visibility and duration are all positive predictors of cycle detectability. We find that when a phenological event lasts >4 wk, an additional 10 yr of data increases cycle detectability by 114 percent and that cycle detectability is 92 percent higher for the most visible events compared to the least. We also find that cycle detectability is four times as high for flowers compared to ripe fruits after 10 yr. To maximize returns in the short‐term, resources for long‐term monitoring of phenology should be targeted toward highly visible phenophases and events that last longer than the observation interval. In addition, programs that monitor flowering phenology are likely to accurately detect regular cycles more quickly than those monitoring fruits, thus providing a baseline for future assessments of change.